Unusual Activation of Cation Disordering by Li/Fe Rearrangement in Triplite LiFeSO4F. Issue 22 (28th May 2018) - Kim, Minkyu; Kim, Minkyung; Park, Heetaek; Li, Hong; Kang, Byoungwoo
Abstract: It is reported that cation disordering in triplite LiFeSO4 F can be activated by Li/Fe rearrangement that results from irreversible and nondestructive structural changes during the 1st charge/discharge cycle, especially during the charge. This rearrangement decreases the number of edge‐shared FeO4 F2 connection environments, compared to the pristine material. With this activation, triplite LiFeSO4 F exhibits several unexpected electrochemical features in subsequent cycles; a decrease in open‐circuit voltage indicating the change in thermodynamic property, negligible volumetric change, enhanced Li diffusion, and facile phase transformation pathway. As a consequence, the cation‐disordered triplite LiFeSO4 F achieves superior rate capability up to ≈66 mA h g −1 at 40 C rate (1.5 min discharge) and has excellent capacity retention for 500 cycles at 5 C charge/5 C discharge rate and for 1200 cycles at 2 C charge/2 C discharge rate. Therefore, triplite LiFeSO4 F can be one of the most promising electrode materials for Li ion batteries. Abstract : Cation disordering in triplite LiFeSO4 F can be activated by Li/Fe rearrangement during the 1st cycle. The activated triplite exhibits much improved electrochemical performance in subsequent cycles.